Myoinositol plus α-lactalbumin supplementation, insulin resistance and birth outcomes in women with gestational diabetes mellitus: a randomized, controlled study - Rosario D’Anna (Nature Portfolio, 2021)
Abstract To verify whether myo-inositol plus α-lactalbumin may reduce insulin resistance and excessive fetal growth in women with gestational diabetes mellitus. In a 12-month period, 120 women with a diagnosis of gestational diabetes mellitus were consecutively enrolled with an allocation of 1:1 in each group and randomly treated with myo-inositol plus α-lactalbumin plus folic acid (treated group) or folic acid (control group) for 2 months. Primary outcome was the variation of insulin resistance through the study evaluated by HOMA-IR. Secondary outcome was the evaluation, through the study, of fetal growth by ultrasound measurements of abdominal circumference centiles and estimated fat thickness. Some clinical outcomes were also considered. After 2 months, in the treated group, a significant reduction in insulin resistance (HOMA values 3.1 ± 1.4 vs 6.1 ± 3.4, p = 0.0002) and fetal growth was shown (Abdominal circumference centiles 54.9 ± 23.5 vs 67.5 ± 22.6, P = 0.006). Among clinical outcomes, a significant decrease in the rate of women who needed insulin (6.7% vs 20.3%, p = 0.03) and of pre-term birth (0 vs 15.2%, p = 0.007) was evidenced. A combination of myo-inositol and α-lactalbumin may reduce insulin resistance and excessive fetal growth. Clinical trial registration: ClinicalTrials.gov, http://www.clinicaltrials.gov , NCT 03763669, first posted date 04/12/2018; last posted date December 06/12/2018.